Mutual solubilization of rosiglitazone and ibuprofen: Investigation and mechanistic insight - Yaxiang Gong; Wenqi Liu (PLoS ONE, 2026)
Purpose We report for the first time that co-dissolved rosiglitazone and ibuprofen mutually enhance their aqueous solubility; the study was designed to quantify this phenomenon and clarify its origin. Methods Solubility was measured by HPLC. Fluorescence and FT-IR spectroscopy were used to probe molecular interactions, while classical molecular dynamics simulations provided atomistic insight. Results The fluorescence intensity of the mixed solution was markedly lower than that of either drug alone, indicating ground-state complexation or close association. FT-IR spectra showed no new peaks, confirming the absence of a new chemical entity or distinct crystal phase. Simulations revealed that each drug increases the solvent–solute compatibility of the other; the resulting hetero-association hinders nucleation and crystal growth, raising apparent solubility. At 30–60 °C, rosiglitazone solubility rose from 60.4–79.9 to 69.2–92.4 μg/mL (+6–16%), while ibuprofen increased from 50.6–89.5 to 56.3–105.0 μg/mL (+11–27%), confirming mutual enhancement. Conclusion The observed mutual solubilization is attributed to specific intermolecular interactions and enhanced solvent compatibility. These findings offer a simple, formulation-free strategy for improving the dissolution of poorly water-soluble drugs.